Hannah Arendt and the history of thought - Brennan, Daniel, 1982-; La Caze, Marguerite (Continental philosophy and the history of thought, 2022)
"This edited collection enriches scholarship on Arendt by considering her contributions to and reflections on the history of thought. The chapters bring Arendt into new conversations with her contemporaries, as well as examining the themes of Arendt's writing in light of her engagement with philosophical and literary history"--